Benthic foraminferal succession in Subic Bay, Philippines the pre- and post- 1991 Pinatubo eruption record - Lucero, Edward Sunga (2003)
Thesis (M.S. Geology)--University of the Philippines Diliman.
"June 2003."
Keywords: Foraminifera -- Philippines -- Subic Bay(Zambales)